Proposta de um sistema de indicadores de ecoinovação para salões de beleza e estética - Blaskovski, Galadriel Sophya (2017)
The beauty and esthetics sector consumes natural resources, industrial chemicals and generates harmful waste to the environment. Thereby, the aim of the present study is to propose a system of eco-innovation indicators, that substantiates a model of environmental management and monitoring in the beauty and esthetic salons. Therefore, the proposal has a conceptual and methodological basis originated with bibliographical survey, which intended to select indicators of environmental innovation and of sustainability suitable for beauty market in Brazil. In order to verify the relevance of the selected indicators, a validation was conducted with researchers of eco-innovation and sustainable innovation by means of a questionnaire sent by electronic mail, produced by Survey Monkey software. The questionnaire consisted of two stages, the first one intended to collect information from respondents, while the second aimed the assessment of the indicators, which were divided into factors: end-of-pipe innovations (1), eco-efficiency (2), innovations of products, process and services (3) and corporate governance indicators (4). Among 75 sent questionnaires, 33 were answered in their entirety. After categorization, the averages of every factor in statistical package SPSS (Statistical Package for Social Sciences) were calculated, in order to verify the consistency of the proposal of indicators and estimate the reliability of the questionnaire, from Alfa of Cronbach. A test of normality of data has also been elaborated, with the coefficients of asymmetry and kurtosis. After validations, the averages were divided into quartiles to identify which were the essential indicators of eco-innovation for beauty and esthetics sector. It has been considered the averages from third and fourth quartiles, which generates a concise and consistent system of indicators. The indicators which had achieved prominence are related to the conscious use of water, to the management of the waste generated in the sector, and to the rational use of chemicals. The factor that presented greater relevance at the analysis was corporate governance, which aims to conduct programs, strategies, initiatives and business plans related to environmental management.